INCREASING CARBON DIOXIDE CONCENTRATION AND TEMPERATURE ON GROWTH AND HISTOPATHOLOGY OF TROPIC MACROALGAE Halimeda sp - . Sahabuddin; Jamaluddin Jompa; Nita Rukminasari (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
The increasing CO2 concentration and temperature affected growth, chlorophyll content, calcium content, and histological tissue of tropical macroalgae Halimeda sp. The study was conducted to examine the interaction effect of the increased CO2 concentration and temperature on growth, chlorophyll-a content, calcium content, and histological tissue of tropical macroalgae Halimeda sp in a laboratory. Research was set with a completely randomized factorial design at 3 levels of factors (A) the CO2 concentration: 385 ppm (ambient), 750 ppm (medium), 1000 ppm (high), and 3 levels of factor (B) the temperature: 30oC, 32oC, 34oC. Microcolony of macroalgae Halimeda sp were selected and obtained from the Lae-lae island then growing in the aquarium 30 x 30 x 45 cm3. Biological parameters observed were growth rate (total, specific and relative), chlorophyll-a content, calcium content, and histopathology tissue. The results showed that the increased of CO2 concentration and temperature negatively affected on the growth of Halimeda sp, reduced of the growth rate, the chlorophyll-a content, calcium content and damaged to histopatology tissue of the Halimeda sp at trophical macroalgae. Keywords: CO2 concentration, temperature, growth response, histopathology, Halimeda sp